2021
DOI: 10.1038/s41467-021-23330-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the DNA damage response phosphatase PPM1D reprograms neutrophils to enhance anti-tumor immune responses

Abstract: PPM1D/Wip1 is a negative regulator of the tumor suppressor p53 and is overexpressed in several human solid tumors. Recent reports associate gain-of-function mutations of PPM1D in immune cells with worse outcomes for several human cancers. Here we show that mice with genetic knockout of Ppm1d or with conditional knockout of Ppm1d in the hematopoietic system, in myeloid cells, or in neutrophils all display significantly reduced growth of syngeneic melanoma or lung carcinoma tumors. Ppm1d knockout neutrophils inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 92 publications
2
11
0
Order By: Relevance
“…For example, PPM1D/Wip1 is a negative regulator of the cancer suppressor p53 and is overexpressed in several human solid cancers. Ppm1d knockout or chemical inhibition of Wip1 in human or mouse neutrophils exacerbates anticancer phenotypes and increases p53-dependent expression of costimulatory ligands and the proliferation of cocultured cytotoxic T cells [ 178 ]. Another study showed that exposure to β-glucan [ 179 ], a fungal-derived prototype agonist of trained immunity, trained neutrophils in mice to enhance the anticancer activity of neutrophils.…”
Section: Neutrophil Plasticity and The Cancer Microenvironmentmentioning
confidence: 99%
“…For example, PPM1D/Wip1 is a negative regulator of the cancer suppressor p53 and is overexpressed in several human solid cancers. Ppm1d knockout or chemical inhibition of Wip1 in human or mouse neutrophils exacerbates anticancer phenotypes and increases p53-dependent expression of costimulatory ligands and the proliferation of cocultured cytotoxic T cells [ 178 ]. Another study showed that exposure to β-glucan [ 179 ], a fungal-derived prototype agonist of trained immunity, trained neutrophils in mice to enhance the anticancer activity of neutrophils.…”
Section: Neutrophil Plasticity and The Cancer Microenvironmentmentioning
confidence: 99%
“…Particularly, the highest cancer type of CCT3 expression in the tumor microenvironment was COAD. As is known to all, the immune cells in tumor microenvironment play a central part in the immunotherapy ( Uyanik et al, 2021 ). Therefore, we wondered the relevance between CCT3 expression and immune characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that inflammatory mediators, important promoters of genetic alterations, play an important role in tumor initiation and progression ( 41 ). Specifically, inflammatory immune cells, such as macrophages and neutrophils, produce a wide variety of reactive substances, which could directly trigger DNA damage of nonimmune cells to further increase mutation frequency and genomic instability ( 42 ). When DNA sustains damage, specific proteins and enzymes are activated to repair such damage ( 43 ).…”
Section: Discussionmentioning
confidence: 99%